Perceived computer self-effcacy of secondary education teachers - Iscioglu, Ersun (My University, 2011)
The main aim of this research was to investigate computer self-effcacy of general secondary education teachers. the population of the study consisted of a total of 98 secondary education teachers working in two different schools located in Famagusta, N.Cyprus. Data collection was made through a Computer Self-Effcacy Scaleff which is developed by Askar and Umay (2001) and a demographic questionnaire. the instrument was applied to all secondary education school teachers in the 2009-2010 terms. According to the results the perceived computer self-effcacy of the teachers is moderate (medium). Furthermore, the results of this research revealed that teachers do not bene't from computer technology either while preparing their lessons, or in the classroom during lecture time, although all of them have computers at home.
Keywords: Computer self-eth cacy; General secondary education teachers; Integration of computer technology into classroom